Appropriateness of antibiotic prescribing among patients treated for dental diseases in Mekelle city, Northern Ethiopia: a cross sectional study - Gebrehiwot Teklay; Haftu Tefera (BMC, 2024)
Abstract Background Local operative treatments are generally preferred for most dental diseases, with antibiotics only recommended as an adjunct in specific cases. Misuse and overuse of antibiotics has been shown to significantly contribute to the development of resistant bacteria. However, the antibiotic prescribing practices of dentists in Ethiopia have not been thoroughly studied. This study aimed to assess the appropriateness of antibiotic prescribing for patients with dental diseases at dental clinics in Mekelle City, Northern Ethiopia. Methods A cross sectional study was conducted in April and May 2020 among patients visiting dental clinics in Mekelle City. Data were collected through patient medical record reviews and dentist interviews. The appropriateness of antibiotic prescription was evaluated based on guidelines from the American Dental Association and the European Society of Endodontology. Data were analyzed using SPSS Statistics, version 29. Binary logistic regression analysis was performed, and the results were presented as odds ratios with 95% confidence intervals. A p value less than 0.05 was considered statistically significant. Results Two hundred and thirty-one patients with dental diseases participated in the study. The mean age was 30.6 years with a standard deviation of 16.1. Most participants had dental pulp related disease. 89% of patients were prescribed antibiotics, with amoxicillin being the most common. Inappropriate antibiotic prescribing was identified in 175 (75.8%) of the study participants. The most common inappropriate prescribing was unnecessary antibiotic prescribing for dental conditions without systemic signs, assessed in 141 (80.1%) participants. Patients diagnosed with pulp related disease without systemic signs and those who had tooth extractions were significantly associated with inappropriate antibiotic prescription (p value < 0.001). Conclusions The study findings show that antibiotics are over-prescribed for dental conditions in this resource constrained setting, especially in patients who have had tooth extractions. Dentists need training on appropriate antibiotic use and antimicrobial stewardship interventions should be implemented in dental setting to reduce unnecessary antibiotic prescriptions and prevent antibiotic resistance development.